Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Low Back Pain(Herniated Lumbar Disc) - Working Group of Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Low Back Pain (Herniated Lumbar Disc); Wei ZHANG; Bidan LOU; Jinxiang LI; Rong LUO; Wenying SHI; Xiaoye LU; Jiang PAN; Jinzhong TANG (康复学报)
Herniated lumbar disc is a common and frequently-occurring disease in clinical practice. In recent years, the incidence rate of herniated lumbar disc has increased and that become younger, which has a negative impact on the life and work of patients. The clinical practice guidelines of traditional Chinese medicine(TCM)rehabilitation for herniated lumbar disc based on evidence-based medicine are of great significance and will help standardize the clinical diagnosis and treatment techniques of TCM and achieve better curative effects. This guideline standardizes the diagnosis and treatment process of herniated lumbar disc from the aspects of scope, terminology and definition, diagnosis, syndrome differentiation, treatment and nursing, in order to provide guidance and reference for re-levant clinicians such as orthopedics and traumatology department of TCM, orthopedics department of integrated traditional Chinese and Western medicine, acupuncture and moxibustion department, massage department, rehabilitation department, etc.①The diagnosis part: the diagnosis starts from six aspects of medical history, symptoms and signs, imaging examination, diagnosis points, differential diagnosis, and syndrome diagnosis, reflecting the characteristics and advantages of TCM syndrome differentiation and treatment.②Rehabilitation assessment: it mainly includes pain assessment, functional impairment assessment, neuromuscular function assessment.③Treatment: it is mainly divided into two parts: non-drug therapy and drug therapy, and the indications and recommended levels of various treatment methods were described in detail. Non-drug therapy mainly includes health education, kinesio therapy, mani-pulation, traction, acupuncture, massage, physical factor therapy, mental health therapy, etc. Drug therapy mainly includes TCM syndrome differentiation treatment, drug therapy(oral medicine, sacral canal closure therapy, epidural injection therapy)and other aspects.④Nursing: it mainly includes diet nursing, daily life nursing, emotional nursing. The guideline could provide guidance for rehabilitation practitioners of different levels and kinds of rehabilitation institutions, traditional Chinese medicine hospitals or general hospitals to carry out rehabilitation treatment of TCM for herniated lumbar disc with good clinical applicability and effectiveness.